DECISION MAKING BY PRINCIPAL BASED ON CROSS-CHANNEL COMMUNICATION MODELS AT SDIT SAMARINDA - Meutia Annisya; Susilo Susilo; Sugeng Sugeng (Magister Manajemen Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2021)
This study aims to determine the implementation of decision-making based on cross-channel communication model, to know the implementation of decision-making based on cross-channel communication model, and to know the changes that occur when applied model of cross-channel communication in decision-making process at Integrated Islamic Elementary School Cordova Samarinda. The method used in this research is case study research with qualitative approach. The results of this study indicate that the principal has a very good ability in communication, both with the superiors, sub-ordinates and surrounding communities and parents of students. In addition, the decision made by the principal is very good by looking at the conditions that occur in the field and remain guided by the vision, mission, and goals to be achieved by the school. Meanwhile, the implementation of cross-channel communication based decision-making is applied very well and undergoes significant changes in accordance with the goal orientation to be achieved by the school.